Affinity of a galactose‐specific legume lectin from Dolichos lablab to adenine revealed by X‐ray cystallography. Issue 7 (21st June 2013) - Shetty, Kartika N.; Latha, Vakada Lavanya; Rao, Rameshwaram Nagender; Nadimpalli, Siva Kumar; Suguna, Kaza
<x xml:space="preserve">Abstract</x> Crystal structure analysis of a galactose‐specific lectin from a leguminous food crop Dolichos lablab (Indian lablab beans) has been carried out to obtain insights into its quaternary association and lectin‐carbohydrate interactions. The analysis led to the identification of adenine binding sites at the dimeric interfaces of the heterotetrameric lectin. Structural details of similar adenine binding were reported in only one legume lectin, Dolichos biflorus, before this study. Here, we present the structure of the galactose‐binding D. lablab lectin at different pH values in the native form and in complex with galactose and adenine. This first structure report on this lectin also provides a high resolution atomic view of legume lectin‐adenine interactions. The tetramer has two canonical and two DB58‐like interfaces. The binding of adenine, a non‐carbohydrate ligand, is found to occur at four hydrophobic sites at the core of the tetramer at the DB58‐like dimeric interfaces and does not interfere with the carbohydrate‐binding site. To support the crystallographic observations, the adenine binding was further quantified by carrying out isothermal calorimetric titration. By this method, we not only estimated the affinity of the lectin to adenine but also showed that adenine binds with negative cooperativity in solution. © 2013 IUBMB Life, 65(7):633–644, 2013